Ms. Kangana Ranaut : brand ambassador or brand destroyer? - Shetty, A. Shivakanth, (SAGE business cases., 2024)
Ms. Kangana Ranaut, a celebrity brand ambassador for LIVA, entered an unwarranted series of controversies due to her independent thinking, outspoken personality, and explicit political beliefs that dragged brands endorsed by her into troubled waters. In a highly charged and divisive socio-political environment like India, a highly opinionated and politically active brand ambassador can also significantly divide consumers who may demonstrate wrath and hatred on the brand’s social media. Brand Manager Mr. Rajeev Gopal must determine whether to continue with a popular celebrity like Ms. Kangana Ranaut or jettison her from the LIVA brand ambassadorship. Will the strong personality of Ms. Kangana Ranaut and her controversies overshadow the very ethos and principles of the LIVA brand? Should brands like LIVA develop their own personality and equity or still ride on the popularity of celebrities, who may occasionally drag brands into troubled waters?